83.8k views
3 votes
If 3(y-1) = y -5. y = ____________.

User Ord
by
4.9k points

2 Answers

4 votes

Answer:

y = -1

Explanation:


3(y-1)=y-5\\\\3y-3=y-5\\\\3y-3+3=y-5+3\\\\3y=y-2\\\\3y-y=y-y-2\\\\2y=-2\\\\(2y=-2)/(2)\\\\\boxed{y=-1}

Hope this helps.

User Manish Ranjan
by
5.0k points
2 votes

Answer:

-1 is the answer

Explanation:

the question is 3(y-1)=y-5

so, we open the bracets and multiply

so it becomes 3y-3 = y-5

now, we transpose

3y-y =-5+3

2y = -2

y= -2/2 = -1

User Alexeypro
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.